Design and Construction of Web Application for Online Management of Electromedical Device Calibration Using Laravel Framework: Rancang Bangun Aplikasi Web Pengelolaan Pengkalibrasian Alat Elektromedis secara Online Menggunakan Framework Laravel - Aji, Hadni Purnama; Prasojo, Ipin; Aprilia, Septi; Siswanto, Hery; Siyamto, Yuli (Politeknik Assalaam Surakarta, 2025)
This study developed a Laravel-based web application to manage electromedical device calibration data online. The application offers greater efficiency and integration compared to manual methods such as Excel or Word. Key features include centralized data storage, cloud integration, and the ability to print calibration certificates directly from the system. Using the R&D method and Blackbox testing, all features were proven to function correctly without errors. User testing also showed that the application is user-friendly and speeds up documentation processes. As a result, the system is expected to enhance the accuracy, efficiency, and professionalism of calibration data management.